1994
DOI: 10.1007/bf03170647
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the effectiveness of Full Option Science System training for third-through sixth-grade teachers

Abstract: Twenty-nine third-and fourth-grade teachers and m,enty-five fifth-and sixth-grade teachers from the Texarkana (Arkansas and Texas) area pubfic schools were trained using the Full Option Science System (FOSS). Participants were given pretests and posttests to measure their: confidence toward teaching science, science content lmowledge, attitude toward teaching science, and attitude toward science. Pretest and posttest results were compared using a paired t-test. The results revealed sigT#ficant gains for both g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 5 publications
0
7
0
2
Order By: Relevance
“…Given the stability of teacher efficacy (see reviews by Ross, 1998; Wolfolk Hoy & Spero, 2005), some researchers reporting an increase in teacher efficacy scores over the duration of a PD program have argued that score improvement is sufficient evidence of a program effect (Bolinger, 1988;Robardey, Allard, & Brown, 1994). The assumption is questionable, particularly if the gains dissipate after the program ends (as found by Ohmart, 1992).…”
Section: Effects Of Pd Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the stability of teacher efficacy (see reviews by Ross, 1998; Wolfolk Hoy & Spero, 2005), some researchers reporting an increase in teacher efficacy scores over the duration of a PD program have argued that score improvement is sufficient evidence of a program effect (Bolinger, 1988;Robardey, Allard, & Brown, 1994). The assumption is questionable, particularly if the gains dissipate after the program ends (as found by Ohmart, 1992).…”
Section: Effects Of Pd Trainingmentioning
confidence: 99%
“…Studies that distinguished PD effects by fidelity of implementation found that teacher efficacy effects were higher for teachers who more diligently applied PD ideas in their classrooms (Fritz et al 1995;Rimm-Kaufman & Sawyer, 2004;Ross, 1994;Stein & Wang, 1988). Second, some of the programs provided for participant interaction (Edwards et al, 1998;Robardey et al, 1994;Ross, 1994), thereby increasing opportunities for vicarious experience (i.e., observing successes of other teachers) and creating settings in which teachers could be persuaded that they would be successful with new teaching strategies. …”
mentioning
confidence: 99%
“…D'ailleurs, plusieurs chercheurs ont observé des effets particulièrement positifs sur le sentiment d'efficacité personnelle des enseignants lorsque les activités de formation visent à les mobiliser dans l'application de stratégies pédagogiques enseignées dans leur pratique professionnelle (Fritz, Miller-Heyl, Kreutzer, & MacPhee, 1995;Lewis, 2001;Rimm-Kaufman & Sawyer, 2004;Ross, 1994;Stein & Wang, 1988). Pour Robardey, Allard et Brown (1994), de même que pour Ross (1994), les programmes ayant prévu des moments d'interactions entre les participants obtiennent également de meilleurs résultats. Ces auteurs rejoignent la thèse de Bandura (2003) voulant que cette modalité d'animation crée des opportunités où les enseignants peuvent témoigner de leur réussite, ce qui constitue un excellent moyen persuasif pour inciter leurs pairs à expérimenter de nouvelles stratégies d'enseignement.…”
Section: Les Effets De La Formation Sur Les Croyances D'efficacité Deunclassified
“…The findings of this study support existing literature on kit-based programming in that they have shown to have a positive impact on student attitudes toward science (Kelly & Staver, 2005;Houston et al, 2008) and provide teachers with tools to enhance science learning (Robardey et al, 1994;Slavin et al, 2014). The limitations of this study do not allow for findings to support existing literature on the positive impact on student achievement (Young & Lee, 2005;Dickerson et al, 2006) because there was no required assessment component to the pilot and the participants did not generally speak to measured academic performance.…”
Section: Hands-on Learningmentioning
confidence: 45%
“…Kit-based science programs have been in circulation since the 1960's (Jones, Robertson, Gardner, Dotger & Blanchard, 2012) and have shown to have a positive impact on student achievement (Young & Lee, 2005;Dickerson et al, 2006), student attitudes toward science (Kelly & Staver, 2005;Houston, Fraser & Ledbetter, 2008), and provides teachers with tools to enhance science learning (Robardey, Allard & Brown, 1994;Slavin, Lake, Hanley & Thurston, 2014). Some widely used kits include FOSS, which were first developed in the late 1980's and pilot tested in San Francisco.…”
Section: Kit-based Science Programsmentioning
confidence: 99%